KENDALA DALAM PELAKSANAAN PROGRAM BANTUAN PELAMPUNG PADA NELAYAN KECIL DI KECAMATAN PADANG UTARA - Adrian Syahputra; Fitri Eriyanti (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2020)
This study is about the effectiveness of the life jacket program in improving the savety assurance of small fisherman in the Padang City. The research method that researchers use is descriptive method and using qualitative approach. This research was conducted in the city of Padang, especially in the District Of North Padang by selecting informants using purposive sampling techniques. Data collected by observation, interview and documentation study. Data validity testing techniques with source triangulation. While the data analysis technique use data reduction techniques, data presentation dan conclusion drawing. The result of this study indicate that the effectiveness of the life jacket program is still not effective. This is because there are still problem in the life jacket program. The problem in this study is the low awareness of fisherman to mitigate or reduce the risk of their woek, the low practicality of the life jacket so that many fishermen do not use them and the lack of supervision from the Padang City Marittime and Fisheries Offic which causes many fishermen who do not use life jacket so that there is no increase in guaratee their safety while at sea.